Unraveling the role of heterotrophic feeding in coral tolerance to ocean warming and microplastic pollution - López Hernández, María Antonieta Panamá; Justus Liebig University Giessen (My University, 2025)
Coral reefs harbor the highest biodiversity of all marine ecosystems and support the livelihoods of nearly 500 million people worldwide. Yet, they are increasingly threatened by global warming. Marine heatwaves disrupt the symbiosis between corals and Symbiodiniaceae algae, leading to coral bleaching. As these algae provide up to 90% of coral energy requirements, their loss results in energy deficits that compromise coral health, reducing growth and reproduction, increasing disease susceptibility, and often leading to mortality. Heterotrophic feeding, as a secondary pathway of energy acquisition in reef-building corals, can sustain up to 100% of their metabolic demands under stress, thereby enhancing survival and resilience to bleaching caused by ocean warming. Consequently, trophic plasticity, i.e., the ability to modulate trophic strategies in response to environmental change, has emerged as a key trait distinguishing potential “winners” under climate change. However, trophic plasticity varies among species and may be compromised by emerging stressors such as microplastic pollution, which can interfere with coral feeding. Despite the importance of heterotrophy in coral resilience, there are still knowledge gaps regarding the role of food type and food availability on coral physiology, and how these interact with pollutants such as microplastic, particularly in an ocean warming context. These uncertainties are further compounded by a lack of field-based data. This thesis addresses these knowledge gaps through two controlled laboratory experiments and the first in situ application of compound-specific isotope analysis of amino acids during a natural bleaching event. Five coral species (Galaxea fascicularis, Porites lobata, Stylophora pistillata, Ctenactis echinata, and Pocillopora verrucosa) were assessed for key physiological traits (photophysiology, growth, energy reserves, δ¹⁵N and δ¹3C), providing a comparative framework of heterotrophic strategies. Results indicated that complex diets enhanced the benefits of heterotrophy across coral species. Although these benefits varied among species when symbiotic, all bleached corals exhibited positive responses to more complex food sources. Physiological rates were consistently higher in symbiotic fragments compared to their bleached counterparts, with the magnitude of these differences increasing alongside the baseline productivity of the species, from G. fascicularis to P. lobata and S. pistillata. Food treatments did not affect respiration or photosynthetic rates, suggesting that growth gains were driven primarily by enhanced heterotrophic nutrient supply. In situ bleaching was associated with δ¹⁵N enrichment in the trophic amino acids alanine (ALA), glutamic acid (GLU), isoleucine (ISO), proline (PRO), and valine (VAL), suggesting alterations in nitrogen acquisition and processing under stress. The trophic position (TP) of the symbiotic host and symbionts of C. echinata was 1.3, consistent with a mixotrophic diet. In contrast, P. verrucosa exhibited TP values of 1.2 for the host and 1.0 for the symbionts, indicating a stronger reliance on autotrophy. Under bleaching, C. echinata maintained a TP of 1.4, reflecting a stable mixotrophic strategy, whereas P. verrucosa shifted to a TP of 1.5, suggesting an increased reliance I on heterotrophy. These findings suggest higher heterotrophic plasticity in P. verrucosa compared to C. echinata. Microplastics (MPs) exposure significantly decreased the energy reserves of P. verrucosa, although it increased photosynthesis and respiration. High food availability partially mitigated the loss of tissue energy content observed while maintaining photosynthesis and respiration rates comparable to control conditions. S. pistillata was not affected by MP exposure alone, but when combined with high feeding, photosynthesis decreased below that of the Control. When exposed to short-term heat stress, all corals bleached severely, however, both species bleached less in the MP treatment suggesting that MPs may also disrupt the relationship between energy balance and thermal resilience. Overall, this thesis provides evidence supporting the central role of heterotrophic feeding in modulating coral tolerance to the combined pressures of ocean warming and microplastic pollution, while emphasizing the need to integrate trophic plasticity and interspecific variability into future conservation and management strategies.
Keywords: ddc:570